Potential of Non-Oil and Gas Exports in Increasing Economic Growth in Indonesia - Gunawan, Agung (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padngsidimpuan, 2024)
This research aims to analyze in more depth the potential for non-oil and gas exports to increase economic growth in Indonesia. This research uses a quantitative approach using survey methods and independent sample t-test analysis to see the relationship and increase in non-oil and gas export data. The population in this study is all oil and gas and non-oil and gas export data with a sample of non-oil and gas exports in 2022 and 2023. The instrument in this study uses structured observation. Meanwhile, statistical data analysis in this study was assisted by SPSS version 26 software. If the data is normally distributed, it will be continued with a parametric statistical test using the t-test, but if the data is not normally distributed, it will be continued with a non-parametric statistical test using the Mann-Whitney test. In this research, the value of non-oil and gas exports in 2022 and 2023 shows that the average value of non-oil and gas exports in 2022 and 2023 is 9.44 and 9.32 with a total of 9.38, while the standard deviation value is 13.55 and 13.92 with a total of 13.54. The results of inferential statistical tests in this research state that the value of non-oil and gas exports in 2022 and 2023, which are reviewed based on January to December, does not have a significant difference.